Associations between Nutrition Knowledge, Vitamin C Intake, Nutritional Status, and Blood Pressure among Elderly with Hypertension in Klaten, Central Java, Indonesia - Triagung Yuliyana; Kusnandar Kusnandar; Diffah Hanim (Faculty of Medicine Universitas Padjadjaran, 2018)
Objective: To analyze the correlation between nutrition knowledge, vitamin C intake, and nutritional status on blood pressure among elderly with hypertension.Methods: This was a cross-sectional study with purposive random sampling which was conducted from April to May 2017. This study included one hundred twenty-five elderly subjects with hypertension who met the inclusion criteria (17 males and 108 females), aged ≥60 years, who lived in the work area of Juwiring Public Health Center in Klaten district, Central Java, Indonesia. The data were analyzed statistically by using normality, correlation, and multiple linear regression tests. Results: The results of the correlation test showed that there was a correlation between nutrition knowledge (p=0.011), vitamin C intake (p=0.012), nutritional status (p=0.048), and blood pressure hypertension in elderly based on the results of multiple linear regression. All data were analyzed statistically using Spearman correlation test to examine the distributed data. A significant correlation was found between nutrition knowledge, vitamin C intake, and nutritional status (p<0.05) using multiple linear regression (p<0.05). A normality test using the Kolmogorov-Smirnov test resulted in normal residue with p-value 0.000. The results showed that the regression analysis could be used to predict the blood pressure.Conclusion: There was a correlation between nutrition knowledge and blood pressure of hypertension in elderly. There was a correlation between vitamin C intake and a blood pressure of hypertension in elderly. There was a correlation between nutritional status and a blood pressure of hypertension in elderly.Keywords: Blood pressure, elderly hypertension, nutrition knowledge, nutritional status, vitamin C intake DOI: 10.15850/ijihs.v6n1.1114